Natural occurrence of nivalenol and mycotoxigenic potential of Fusarium graminearum strains in wheat affected by head blight in Argentina - Fernandez Pinto, V.E. (2008)
The principal agents of Fusarium head blight in the main cropping area of Argentina were investigated in heavily infected samples. The ability of the isolates to produce trichothecenes was determined by GC and HPLC. Fusarium graminearum was the predominant species and of 33 isolates, 10 produced deoxinivalenol (DON) (0.1- 29 mg kg-1), 13 produced both deoxinivalenol (1.0- 708 mg kg-1) and nivalenol (0.1- 6.2mg kg -1), 12 produced 3-acetyldeoxinivalenol (0.1- 14 mg kg-1), 13 produced 15-acetyldeoxinivalenol (0.1- 1.9 mg kg-1), 10 produced Fusarenone X (0.1- 2.4 mg kg-1) and 7 produced zearalenone (0.1- 0.6 mg kg-1). These results suggest that F. graminearum strains isolated from the wheat growing regions in Argentina belong to DON chemotype. Although some strains produced both deoxinivalenol and nivalenol, nivalenol was produced in lower levels. The natural occurrence of nivalenol in wheat affected by head-blight collected in the main production area during two years (2001-2002) was also determined. From 19 samples 13 were contaminated with deoxinivalenol in a range of 0.3 to 70 mg kg-1 and 2 samples with both deoxinivalenol (7.5 and 6.7 mg kg-1) and nivalenol (0.05 and 0.1 mg kg -1), respectively. This is the first report of natural occurrence of nivalenol in wheat cultivate in Argentina.